DEVELOPMENT OF INTERACTIVE DIGITAL WEBSITE USING LEARNINGAPPS TO DEVELOP VOCABULARY FAMILIE THEME LEVEL A1 - Putri Roganda Pane; Enggis Br Siagian; Melani Limbong; Shelomita Adinda; Naia Rencani Suci (SMART: Journal of Multidisciplinary Educational, 2024)
This study aims to evaluate the impact of using interactive web-based learning media through LearningApps on the improvement of German vocabulary mastery at the A1 level at Universitas Negeri Medan. The research method employed is developmental research using Thiagaraja's theory, which includes four stages: planning, creation, trial, and evaluation. The results indicate that the use of LearningApps significantly enhances students' vocabulary mastery, with an average increase in vocabulary test scores of 35% compared to conventional learning methods. Additionally, 86% of students reported increased learning motivation and higher engagement in the learning process. The main challenges identified include accessibility limitations and the need for curriculum adaptation. The study also found that the use of LearningApps can improve interaction and collaboration among students, making the learning process more enjoyable and effective. These findings suggest that interactive digital learning media like LearningApps have great potential to enhance the quality of language learning, but strategies are needed to address accessibility and curriculum adaptation challenges.